Age at migration and the risk of psychotic disorders: a systematic review and meta‐analysis. (20th January 2020) - Anderson, K. K.; Edwards, J.
Abstract : Objective: To conduct a systematic review and meta‐analysis of the existing evidence on the association between age at migration and the risk of psychotic disorders. Methods: Observational studies were eligible for inclusion if they presented data on the association between age at migration and the risk of psychotic disorders among first‐generation migrant groups. We used two random effects meta‐analyses to pool effect estimates for each stratum of age at migration relative to (i) a native‐born reference category and (ii) the youngest age stratum (0 to 2 years). Results: Ten studies met inclusion criteria, and five were included in the meta‐analysis. The risk of psychotic disorder among people who migrate prior to age 18 is nearly twice as high as the native‐born population, with no evidence of effect modification by age strata. People who migrate during early adulthood (19 to 29 years) have a similar risk of psychotic disorder as the native‐born population (IRR = 0.93, 95% CI = 0.60, 1.44) and a lower risk relative to those who migrate during infancy (0 to 2 years) (IRR = 0.58, 95% CI = 0.33, 1.04). Conclusions: Migrant status is one of few well‐established risk factors for psychotic disorder, yet we have limited understanding of the underlying etiology. The findings of this review advance our understanding of this association and identify high‐risk groups to target for intervention.